2000
DOI: 10.1287/trsc.34.4.426.12325
|View full text |Cite
|
Sign up to set email alerts
|

Diversion Issues in Real-Time Vehicle Dispatching

Abstract: Recent technological advances in communication systems now allow the exploitation of realtime information for dynamic vehicle routing and scheduling. It is possible, in particular, to consider diverting a vehicle away from its current destination in response toIn the past few years, there has been a rapid growth in communication and information technologies (e.g., global positioning satellites, cellular phones, geographic information systems, geosynchronous satellite-based systems, etc.). These recent advances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
117
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(120 citation statements)
references
References 23 publications
1
117
0
2
Order By: Relevance
“…Once a customer of a vehicle has been served, the best solution found up to now is used to determine the next stop for the particular vehicle and all other current solutions are updated correspondingly. Based on the same tabu search heuristic, in a subsequent paper, Ichoua, Gendreau, and Potvin (2000) examine the benefit of allowing a vehicle to change its destination while under way from one scheduled customer to the next in order to service a newly arrived customer. Empirical tests show a reduction in the number of unserved customers and in the combined objective function addressing the distance traveled and the total lateness, if diversion is allowed.…”
Section: Related Workmentioning
confidence: 99%
“…Once a customer of a vehicle has been served, the best solution found up to now is used to determine the next stop for the particular vehicle and all other current solutions are updated correspondingly. Based on the same tabu search heuristic, in a subsequent paper, Ichoua, Gendreau, and Potvin (2000) examine the benefit of allowing a vehicle to change its destination while under way from one scheduled customer to the next in order to service a newly arrived customer. Empirical tests show a reduction in the number of unserved customers and in the combined objective function addressing the distance traveled and the total lateness, if diversion is allowed.…”
Section: Related Workmentioning
confidence: 99%
“…Recent surveys on dynamic VRP can be found in [19,20,28]. Tabu search [23], genetic algorithm [21], assignment, and insertion-based heuristics [17], approximate dynamic programming [31], and nearest-vehicle based heuristic [16] have been proposed to consider online requests and uncertain travel time in the dynamic VRP problem. Yang et al [34] have developed a general framework for the dynamic vehicle routing problem in which new requests can arrive during operations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Since vehicle breakdowns have not been explicitly considered in train rescheduling [11,26], dynamic VSP [22], or dynamic VRP [16,17,21,23,31,34], most of results available are not directly applicable to our problem. Although aircraft breakdown is considered in some studies of airline operations recovery, most of the available algorithms [8,25,29,32] involve a small number of trips and aircrafts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Madsen et al (1995) suggested a heuristic algorithm for a dial-a-ride problem, which is one example of a dynamic vehicle-routing problem. Ichoua et al (2000) addressed a real-time vehicle-dispatching problem with a diversion possibility in which diverting a vehicle away from its current destination in response to a new customer request is allowed. Fischer et al (1996) suggested a multi-agent approach for solving transportation problems.…”
Section: Introductionmentioning
confidence: 99%